The arena or E-games triathlon as a unique real world and virtual mixed-model endurance sports event - Stapley, Paul J.; Lepers, Romuald; Heming, Tim; Gremeaux, Vincent (Frontiers in Sports and Active Living, 2024)
The sport of triathlon has evolved to become a discipline comprising races of different lengths and formats. It has also undergone significant growth in popularity and exposure with several variations in format from the classic swim -bike -run combination attracting significant television and media coverage. Since 2021 an original and unique format called the Arena Games Triathlon (or in 2024 the E-Games) has evolved that involves athletes competing against each other in swimming, cycling and running combining both the real and virtual worlds in one race. This model of endurance sport is currently unique, provides instantaneous data on performance and has the potential to be a tool for performance prediction, talent selection and sport development. The goal of this perspective paper is to provide context around the emergence of the Arena Games Triathlon series, describe the format of this type of racing, outline how it has the potential to drive training and evaluation of triathletes and discuss the attractiveness of its future inclusion as an Olympic discipline.